The influence of school environment and the performance of the honorary teachers of Islamic education toward the learning achievements - Milya Angreranti; Noor Malihah (Institut Agama Islam Negeri (IAIN) Salatiga, 2018)
This research aims to know the influence of school environment and the performance of the honorary teachersof Islamic Education inSD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward the students' learning achievements. The study as designed as a research survey using quantitative methods (implementing partial regression or double recreation). The respondents are the fifth-grade students of SD Negeri Jetis I and SD Negeri Nampu I Karangrayung. The findings show that (1) there is a positive influence of school environment in SD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward the students' learning achievement as much as 2.7%. It means if the school environment is increased by one point then the students' learning achievements will be increased by 2.7%, (2) there is a positive influence on the performance of the honorary teacher Islamic Education in SD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward the students' learning achievement as much as 13.7%.This means if the performance of the honorary teachersIslamic Education is increased by one point then the students' learning achievements will be increased by 13.7%, and (3) there is a positive influence of school environment and the performance of the honorary teachersIslamic Education in SD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward students' learning achievement as much as 13.7%.